Evaluating the Impacts of Local Economic Development Policies On Local Economic Outcomes: What Has Been Done and What is Doable? - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2002)
This paper argues that more rigorous evaluations of local economic development policies are feasible. Programs that aid selected small firms can be rigorously evaluated using an experimental approach, without excluding firms from assistance, by randomly assigning some firms to receive more intense marketing efforts by the program. Programs that aid distressed local areas can be rigorously evaluated by random assignment of the program among eligible distressed areas. If an experiment cannot be done, a variety of statistical approaches can be used to compare firms or areas that use the program with comparison groups of firms or areas that do not use the program. These statistical analyses should be supplemented with surveys and focus groups with businesses that use the program, which give some insight into why the program works or doesn't work. Evaluations should go beyond the effects of programs on business growth to effects on local fiscal health and the earnings of the unemployed. Evaluations using rigorous approaches suggest that programs providing information services to small manufacturers are frequently effective. Programs targeting distressed areas are ineffective unless great resources are used over a lengthy period.
Additional information: A revised version of this paper appears in Evaluating Local Economic and Employment Development: How to Assess What Works among Programmes and Policies. 2004. Paris: OECD.
Keywords: R11; R50; H43; H70; 330; evaluation; local; regional; economic; development; Bartik